Harnessing the Biology of Canine Intestinal Organoids to Heighten Understanding of Inflammatory Bowel Disease Pathogenesis and Accelerate Drug Discovery: A One Health Approach - Kopper, Jamie J.; Iennarella-Servantez, Chelsea; Jergens, Albert E.; Sahoo, Dipak K.; Guillot, Emilie; Bourgois-Mochel, Agnes; Martinez, Marilyn N.; Allenspach, Karin; Mochel, Jonathan P. (Frontiers in Toxicology, 2021)
In a recent issue of the Lancet, the prevalence of Inflammatory Bowel Disease (IBD) was estimated at 7 million worldwide. Overall, the burden of IBD is rising globally, with direct and indirect healthcare costs ranging between $14.6 and $31.6 billion in the U.S alone in 2014. There is currently no cure for IBD, and up to 40% of patients do not respond to medical therapy. Although the exact determinants of the disease pathophysiology remain unknown, the prevailing hypothesis involves complex interplay among host genetics, the intestinal microenvironment, and the mucosal immune system. Importantly, multiple chronic diseases leading to high morbidity and mortality in modern western societies, including type II diabetes, IBD and colorectal cancer, have epidemiologically been linked to the consumption of high-calorie, low-fiber, high monosaccharide, and high-fat diets. However, progress in our understanding of the effect of dietary interventions on IBD pathogenesis has been hampered by a lack of relevant animal models. There remains, therefore, a critical need to develop translatable in vitro and in vivo models that faithfully recapitulate human gut-specific physiological functions. Noteworthily, abundant literature suggests that canine and human IBD share common clinical and molecular features, such that preclinical studies in dogs with naturally occurring IBD present an opportunity to further our understanding on disease pathogenesis and streamline the development of new therapeutic strategies. Using a stepwise approach, in vitro mechanistic studies investigating the contribution of dietary interventions to chronic intestinal inflammation and “gut leakiness” could be performed in 3D intestinal organoids. Likewise, the effect of therapeutic drug candidates could be evaluated in 3D organoids prior to longitudinal studies in dog and human patients with IBD. In this review, we will discuss the value (and limitations) of 3D intestinal organoids derived from a spontaneous animal disease model of IBD (i.e., the dog), and how it can heighten understanding of the interplay between dietary interventions, the gut microbiota and intestinal inflammation. We will also review how 3D intestinal organoids could be used to streamline the preclinical development of therapeutic drug candidates for IBD patients and their best four-legged friends.